Investigation of people familiarity towards virtual tourism as an alternative to travel - Rafidola Mareta Riesa; Alfatah Haries (International Ecsis Association, 2022)
The COVID-19 pandemic has brought the development of the tourism industry to a very low point. With social restrictions, people are expected not to travel in advance and can keep their distance. This research aims to further deepen public understanding regarding virtual tourism and its use in the city of Padang during the lockdown at various tourist objects. This research found that the government introduced virtual tourism as an alternative amid distance restrictions, because tourist can enjoy the tourism object without having to be physically present. The availability of many media that can be used as tools in displaying virtual tourism. This research provides suggestions so that the relevant government can provide socialization to the community so that virtual tourism can be used as an alternative to traveling during the COVID-19 pandemic.